Modifikasi Kulit Telur Puyuh Dan Fly Ash Menjadi Katalis Cao/Fly Ash Untuk Reaksi Transesterifikasi Minyak Sawit Off Grade Menjadi Biodiesel - Simbolon, Kristin Madelin; Helwani, Zuchra; Irianty, Rozanna Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Quail eggshells CaO based catalyst with the addition of fly ash has been successfully synthesized for production of biodiesel from palm oil off-grade. Quail eggshells waste modificated of solid base catalyst through calcination, hydration, dehydration methods with fly ash through impregnation method to load calcium oxide with quail eggshells as precursor.The catalyst was characterized by X-Ray Diffraction (XRD) and basic strength while the characterization of biodiesel was by Gas Chromatography-Mass Spectrometry (GC-MS). The catalyst was synthesized by calcining the quail eggshells as source of CaCO3 at calcination temperature of 900 oC for 2,5 hours. The CaO was then supported by fly ash. The catalyst with the highest catalytic activity was obtained at dehydration temperature of 500 oC and the dehydration time of 4 hours with transesterification reaction conditions of a molar ratio of methanol/oil 6:1, catalyst concetration of 6%-b oil and temperature of 70 °C for 2 hours with yield biodiesel results reached 85,12%.Keyword: biodiesel, calcium oxide, catalysts, fly ash, transesterification